Immunological detection of large oxidized lipoproteins in hypertriglyceridemic serum. (September 2013) - Sakurai, Toshihiro; Wada, Norio; Takahashi, Yuji; Ichikawa, Ayako; Ikuta, Akiko; Furumaki, Hiroaki; Hui, Shu-Ping; Jin, Shigeki; Takeda, Seiji; Fuda, Hirotoshi; Fujikawa, Masato; Shimizu, Chikara; et al.
Background: Triglyceride-rich, low-density lipoproteins (TG-rich LDL) have been reported as an oxidized lipoprotein species in patients with severe liver disease. Using TG-rich LDL as an immunogen, we obtained a monoclonal antibody (G11-6) that reacted with TG-rich LDL from patients with liver disease and with metal-oxidized LDL only in the early process of the oxidation reaction. This study determined the G11-6-reactive lipoproteins in hypertriglyceridemic serum. Methods: Serum samples from healthy volunteers ( n  = 12) and hypertriglyceridemic patients ( n  = 9) were fractionated by gel filtration and subjected to a sandwich enzyme-linked immunosorbent assay (ELISA) using G11-6 and polyclonal anti-apolipoprotein B antibodies. Results: Small LDL and larger lipoproteins reacted with G11-6. G11-6-reactive small LDL was identified in both the healthy subjects and hypertriglyceridemic patients, whereas G11-6-reactive larger lipoproteins were found only in the hypertriglyceridemic patients. Conclusions: G11-6 is a useful tool for detecting increased large oxidized lipoproteins in hypertriglyceridemic patients.